PRODUCTIVE AND QUALITATIVE CHARACTERISTICS OF CORN HYBRIDS FOR SILAGE PRODUCTION - RENIUS MELLO; JOSÉ LAERTE NÖRNBERG; MARTA GOMES DA ROCHA; DIEGO BITENCOURT DE DAVID (Revista Brasileira de Milho e Sorgo, 2005)
The study of corn genotypes available in the market is of great interest for producers and researchers of the animal and agronomic science. The objective of this trial was to evaluate the productive and qualitative potential of corn hybrids for silage production. The treatments consisted of six corn hybrids: DKB-215, DKB-344, C-747, AS-32, BR-201 and OC-705. The variables analyzed were: height (m), fresh and dry matter yields (FMY and DMY, t ha-1), contribution of each structural component of the plant (stem, leaves and ears), dry matter content (DM), pH, ammoniacal nitrogen as percentage of the total nitrogen (NH3-N%/TN), cell wall composition (NDF, HEM, ADF, CEL, ADL), organic matter (OM), crude protein (CP), ether extract (EE), total carbohydrates (TC), non-fiber carbohydrates (NFC), digestible neutral detergent fiber (NDFd), digestibility of the neutral detergent fiber (DNDF), calcium (Ca), phosphorus (P), potassium (K), magnesium (Mg), in vitro dry matter digestibility (IVDMD) and total digestible nutrient (TDN). A randomized block design, with six treatments and four replicates was used. The FMY and DMY differed (P <0.05) among hybrids, with values oscillating between 16.24 to 30.77 and 6.64 to 11.31 t ha-1, respectively. The OC-705 and DKB-344 hybrids obtained the largest (P<0.05) DMY. The DKB-215, DKB-344 and C- 747 hybrids presented larger (P<0.05) ear contribution in the biomass. Stems NDF showed similar results to leaves, however the ADL values were smaller. The DM content at ensiling oscillated between 33.46 and 43.89 %, with a normal fermentative process, presenting pH and NH3-N%/TN values oscillating among 3.57 to 3.68 and 3.01 to 3.90, respectively. The OM, CP, ADL, NDFd and TC content did not differ (P>0.05) among silage of the different hybrids. Silage of the hybrid DKB-344 showed smaller percentage of NDF and ADF. The silage of the hybrids DKB-215 and DKB-344 had higher digestibility (DNDF and IVDMD) and energy content (TDN). Silage of all hybrids presented adequate fermentative process. However, in the univariate analysis of variance, DKB-344 hybrid showed higher yield and better quality, while in the multivariate analysis of variance, DKB-215 hybrid was the most recommended for the silage production.